THE ROLE OF PBV AS MODERATION OF CAGR, ROE, AND DER ON SHARE PRICE - Khotmi, Herawati; Savira, Anisa; Fachrozi, Fachrozi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
This study examines the factors affecting stock prices in Islamic banking sector companies listed on the IDX for 2021-2022, with Price Book Value (PBV) as amoderating variable. The research method used is quantitative, with a sample of 3 Islamic banks listed on the IDX, including PT Bank Syariah Indonesia Tbk, PT Bank BTPN Syariah Tbk, and PT Bank Panin Dubai Syariah Tbk. The results of the study state that CAGR (Compound Annual Growth Rate) has a positive effect on stock prices and DER (Debt to Equity Ratio) has a negative effect on stock prices, with the results of 0.035 (CAGR) and 0.001 (DER) <0.05. Meanwhile, ROE (Return on Equity) and PBV (Price to Book Value) do not affect stock prices, with a significance value of 0.401 (ROE) and 0.246 (PBV) > 0.05. All variables influence stock prices with a significance value of 0.000 <0.05. PBV as a moderator can only moderate DER with a p-value of 0.0081 <0.05. PBV does not moderate CAGR and ROE because their p-value is > 0.05.